ANXIETY AND DEPRESSION IN CANCER PATIENTS: ASSOCIATION WITH CLINICAL ASPECTS AND ADHERENCE TO ONCOLOGICAL TREATMENT - Machado, Lara Cândida de Sousa; Guimarães, Isadora Maria de Oliveira; Leão, Lívia Caetano da Silva; Silva, Gilson Gonçalves; Camargo Júnior, Elton Brás (Cogitare Enfermagem, 2024)
Objective: to identify symptoms of anxiety and depression in cancer patients and their association with clinical aspects and adherence to oncological treatment. Method: a cross-sectional study with a convenience sample conducted between September 2020 and May 2021, including patients diagnosed with cancer from all regions of Brazil. The instruments used were the Hospital Anxiety and Depression Scale and the Morisky Test. Multivariate logistic regression analyses were conducted to verify associations. Results: the sample included 69 patients, of whom 69.6% presented anxiety, and the same proportion presented depression. Simultaneous anxiety and depression were present in 59.4% of the cases. Anxiety was associated with the presence of fatigue. Depression was associated with the time of diagnosis, asthenia, and treatment location. The simultaneous occurrence of anxiety and depression was associated with asthenia and treatment location. Conclusion: high levels of anxiety and depression underscore the need to implement psychosocial support interventions for cancer patients.